2008
DOI: 10.1177/1090198108314619
|View full text |Cite
|
Sign up to set email alerts
|

Healthy Youth Places: A Randomized Controlled Trial to Determine the Effectiveness of Facilitating Adult and Youth Leaders to Promote Physical Activity and Fruit and Vegetable Consumption in Middle Schools

Abstract: The Healthy Youth Places (HYP) intervention targeted increased fruit and vegetable consumption (FV) and physical activity (PA) through building the environmental change skills and efficacy of adults and youth. HYP included group training for adult school site leaders, environmental change skill curriculum, and youth-led FV and PA environment change teams. Sixteen schools were randomized to either implement the HYP program or not. Participants (N =1,582) were assessed on FV and PA and hypothesized HYP program m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
149
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 95 publications
(152 citation statements)
references
References 24 publications
1
149
0
2
Order By: Relevance
“…However, our baseline data demonstrated that sites did not deliver the school district's menu as intended. 17 Furthermore, interviews corroborated baseline data, indicating that there was wide variability in snack offerings between after-school programs. In both years, all participants reported that the goal of FV being offered at every snack was not met.…”
Section: Daily Healthy Snackmentioning
confidence: 71%
See 4 more Smart Citations
“…However, our baseline data demonstrated that sites did not deliver the school district's menu as intended. 17 Furthermore, interviews corroborated baseline data, indicating that there was wide variability in snack offerings between after-school programs. In both years, all participants reported that the goal of FV being offered at every snack was not met.…”
Section: Daily Healthy Snackmentioning
confidence: 71%
“…The lead author developed themes for an initial coding guide based on the interview guide, knowledge (from transcribing the interviews), and was organized based on an ecologically informed social cognitive approach that informed the HOP'N after-school program. [15][16][17] A social ecological approach 20 allowed coders to illustrate staff (individual) and organizational influences on implementation. After the initial development of the coding guide, four experts reviewed it, and the guide went through several revisions.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations